2022
DOI: 10.1155/2022/6338221
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of the Cultural Diversity Effect by Using Picture Books with a Preschool Teacher

Abstract: Cultural diversity is endorsed by many educators as a major teaching concept due to its significance for the achievement of social equity in education. Recently, the use of picture books to promote principles related to cultural diversity has become a rising trend in early childhood settings. This study examined Chinese preschool teachers’ attitudes toward using picture books to teach cultural-diversity-related topics and their reported practices. Seven preschool teachers from four institutions located in Shan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Field trips, which allow children to make observations and raise awareness, support the acquisition of first-hand experience (Leback, 2007). In the qualitative findings of a study examining preschool teachers' attitudes and practices towards using picture books to teach cultural diversity (Zhang, 2022), it was reported that picture books alone are not enough to explain cultural diversity, and that they should be planned together with field trips that will enable children to gain first-hand experience. Learning through experience can help children learn about cultural diversity and help them lose prejudices by interacting with individuals from different cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Field trips, which allow children to make observations and raise awareness, support the acquisition of first-hand experience (Leback, 2007). In the qualitative findings of a study examining preschool teachers' attitudes and practices towards using picture books to teach cultural diversity (Zhang, 2022), it was reported that picture books alone are not enough to explain cultural diversity, and that they should be planned together with field trips that will enable children to gain first-hand experience. Learning through experience can help children learn about cultural diversity and help them lose prejudices by interacting with individuals from different cultures.…”
Section: Discussionmentioning
confidence: 99%